2022
DOI: 10.23910/1.2022.2870
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis for Assessment of Yield Performance and Adaptability of Selected Mango (Mangifera indica L.) Genotypes under Multi Location Trials in India

Abstract: A study was conducted in April 2020 based on the data collected from the All-India Coordinated Research Project on Sub-Tropical Fruits (AICRP-STF) and Central Institute for Subtropical Horticulture (CISH), Lucknow, India. The objective was to identify the high yielding and stable genotypes of mango using Additive main effects and multiplicative interaction (AMMI) and Genotype plus Genotype×Environment interaction (GGE) biplot analyses. Data on sixteen genotypes of mango tested across four locations, viz., Rewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In Nigerian cashew breeding programme, Aliyu et al, (2014) reported variation explained by genotype of 53.53%, environment of 4.35% and G×E interaction of 24.69%. In mango which belongs to cashew family Anacardiaceae, the variation explained by genotypes, environments and G×E interaction were 6.95%, 37.78%, and 42.81% (Krishna et al, 2022). The differences in cashew and mango could be attributed to differences in the genotypes and the effect of environment.…”
Section: Discussionmentioning
confidence: 99%
“…In Nigerian cashew breeding programme, Aliyu et al, (2014) reported variation explained by genotype of 53.53%, environment of 4.35% and G×E interaction of 24.69%. In mango which belongs to cashew family Anacardiaceae, the variation explained by genotypes, environments and G×E interaction were 6.95%, 37.78%, and 42.81% (Krishna et al, 2022). The differences in cashew and mango could be attributed to differences in the genotypes and the effect of environment.…”
Section: Discussionmentioning
confidence: 99%